Efficient dynamic mechanisms in environments with interdependent valuations: The role of contingent transfers - Heng Liu (Theoretical Economics, 2018)
This paper addresses the problem of implementing socially efficient allocations in dynamic environments with interdependent valuations and evolving private information. In the case where the agents' information is correlated across time, we construct efficient and incentive compatible direct dynamic mechanisms. Unlike the mechanisms with history-independent transfers in the existing literature, these mechanisms feature history-dependent transfers. Moreover, they are reminiscent of the classical Vickrey-Clarke-Grove (VCG) mechanism, even though the latter is not incentive compatible with interdependent valuations. We further show that the VCG aspect of the direct mechanisms suggests natural ways for implementation in some repeated auctions.
Keywords: C73; D61; D82; 330; Dynamic mechanism; interdependent valuation; intertemporal correlation